(3GdaJMI GdCfSjI dZdb GdJMaI GdbOSjIs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s
(3ChdgG (B:s
(3GdMeO def bSeJg Ydi GdOhGe YGOdI hHYO aEf GdJMaI GdbOSjI ai GNJUGQ GdQLjHI ai GdaQGV fXe GdYdGeI Hf GdgGFe Cf CTQMgG hSejJg s
(3BNQgG (B:s
(3dCf GdJPcQ ehLhO hEf de jYde Yjfg adG JhGQK cGdbSejf GdChdjf hai agegeG ef GdfXe JYSa Ci fUagG eHjfI hGdMeO ddg Ydi GdJeGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf ai L(B1 (3U (B372 (3Cf GdJMaI GdbOSjI ai GNJUGQ GdQLjHI gi deDdagG CHh GdYHGS CMeO Hf eMeO Hf GdgGFe GdTGaYi gi d` eMeO Hf Ydi Hf GdMSjf GdQLHi GdeYQha HGHf GdeJbfI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs